Region-specific gut microbiota and metabolite crosstalk underlie feed efficiency variation in Strongylocentrotus intermedius - Lin Cong; Yuehan Yan; Yu Guan; Jialiang Dong; Ziling Qin; Yi Zheng; Zhe Song; Tianqi Wang; Xiaotong Wang; Wenchao Yu (Aquaculture, 2027)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Site-specific promoter hypermethylation of GPX4 in heart failure with reduced ejection fraction (HFrEF): nonlinear dose-response with hepatic and coagulation markers - Lin Ma; Xiangwen Li; Dandan Zhang; Li Song; Yu Guo; Leyi Wang; Rongqiang Zhang (Molecular Biology Reports, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

Biostratigraphic and paleobiogeographic significance of two cap-shaped fossil groups from the Cambrian Xinji Formation, North China: Evidence for North China–Australia faunal links - Meng Gong; Hong Hua; Yang Hou; Xinzi Wang; Song Zhang; Zihui Wu; Xueting Wang; Ling Yu; Yan Tan; Jinzhou Luo; Lin Bai (Journal of Asian Earth Sciences, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

A new biostratigraphic marker for Cambrian Stage 3 on the Northern Margin of the Yangtze Platform: Mianxiantubus–Pelagiella subangulata assemblage subzone - Xueting Wang; Hong Hua; Jinzhou Luo; Yang Hou; Meng Gong; Song Zhang; Xinzi Wang; Zihui Wu; Yan Tan; Ling Yu; Lin Bai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Determining the trends and drivers of extreme flow in permafrost rivers - Zhiwei Wang; Genxu Wang; Huaiyong Shao; Chunlin Song; Shan Lin; Gang Liu; Zheng Jin; Chen Yu (Journal of Hydrology, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Ultrasensitive and rapid detection of botulinum neurotoxin serotype A via Argonaute-mediated signal cascade with a pregnancy test strip readout - Weiling Yu; Yukang Chen; Shujie Zhang; Ruina Zheng; Zhanyin Lin; Yujun Mei; Qiancheng Zhan; Bowen Xue; Jinxuan Fan; Bo Liu; Song Gao; Yuan-Di Zhao; et al. (Food Chemistry, 2026)

Compression and shear stability capacity design for a composite wall combining concrete-filled steel tubes and corrugated steel plates - Xiang-Yu Zhao; Yan-Lin Guo; Ke Wang; Jin-Song Duan; Wen-Ke Zheng (Engineering Structures, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Skin temperature as input to behavioral thermal adaptation for energy-efficient HVAC control - Yu Dong; Yuan Shi; Yanfeng Liu; Cong Song; Bintian Lin; Jørn Toftum (Energy and Buildings, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Cascade delivery and synergistic ferroptosis-apoptosis induction via hybrid-membrane-coated MOF nanoparticles for glioblastoma therapy - Yue Huang; Zesheng Sun; Guiping Jiang; Qianqian Liu; Jialiang Lin; Song Deng; Yan Song; Yu Yang; Yinhao Chen; Yi Wang; Rongqin Huang; Jinlong Shi (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Secondary aerosol formation Would Promote the Formation of Ozone: Evidence from a Yangtze River Delta campaign - Gang Zhao; Jinyuan Yu; Song Guo; Min Hu; Linghan Zeng; Weili Lin; Chunsheng Zhao (Atmospheric Environment, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Arbuscular mycorrhizal fungi as soil biota improve soybean nutrient acquisition and yield formation: a global meta-analysis - Ying-chun Du; Qiong Hou; Yu-qi Song; Lin Wang (Rhizosphere, 2026)

Early-stage targeted low-dose chlorine-bentonite treatment for cyanobacterial bloom control in deep reservoirs - Xi Li; Shengda Wang; Weijun Song; Bastiaan W. Ibelings; Yiruo Xia; Miquel Lürling; Nesrine Imene Hame; Hichem Nasri; Viktor A. Gabyshev; Andrey Yu. Krasnopeev; Olga I. Belykh; Na Lin; et al. (Journal of Hazardous Materials, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

ROS-responsive “Trojan Horse” nanoplatform via homotypic fibroblast-membrane camouflage for precision reprogramming of pathogenic synoviocytes in rheumatoid arthritis - Hua-Zhong Ying; Zhen-Hua Ying; Zhi-Min Rao; Song-Lin Jiang; Song-Zhao Zhang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Chen-Huan Yu (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

RGI-Net: A Recursive Gated Injection Network for Underwater Image Restoration in Marine Inspection - Yu Lin; Mingming Wen; Shuiyuan He; Laiyong Song (Journal of Marine Science and Engineering, 2026)
Background: Underwater optical imagery used in marine inspection is degraded by wavelength-dependent attenuation and scattering, which couple color cast with structural haze. Existing restorers either treat both degradations in one stage or cascade separate networks and exchange information only through reconstructed images. Methods: This paper proposes RGI-Net, combining (i) a shared-weight two-pass pipeline that disentangles Lab chromatic correction from RGB structure refinement without duplicating the backbone and (ii) a 1×1 Gated Injection Bridge that transfers Pass-1 bottleneck features into Pass 2 under a learned element-wise gate, together with a recursive contrastive objective that includes a cross-pass consistency term. All methods are compared on identical test partitions under one evaluation pipeline (UIEB train/test, LSUI, EUVP, U45, C60). Results: Against WaterNet, PUIE-Net, CCL-Net, and Phaseformer, RGI-Net attains the best UIEB UIQM (2.21) and UCIQE (0.372), with PSNR/SSIM statistically indistinguishable from Phaseformer (Wilcoxon p>0.5). On the reported GPU, wall-clock latency is 41.00 ms, versus 61.64 ms for Phaseformer at 256×256, while RGI-Net has the largest parameter count and FLOPs in the comparison. Conclusions: Shared two-pass decoupling with gated bottleneck injection improves UIEB no-reference indices. Lower latency than Phaseformer on one workstation GPU is not a claim of overall computational efficiency, given the larger parameter and FLOP counts. UIQM and UCIQE are operational scores, not perceptual or inspection-task evidence; on EUVP, the best UIQM/UCIQE coincide with the lowest PSNR/SSIM among compared methods, which remains a substantial limitation.

Construction and validation of plant configuration methods for coastal wetland parks under the close-to-nature concept - Ying Lin; Xiaoli Song; Qingyun Yu; Yunjia Kang; Yanchuan Yang; Peiyan Guo; Xiaolei Jiang (Landscape and Ecological Engineering, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

U-UNO: An enhanced neural operator-based deep-learning model for 3D velocity field inversion - Qianggong Song; Jiabin Yu; Puyi Hou; Ye Lin (Journal of Applied Geophysics, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

The role of exogenous electron donors in steering microbial electrosynthesis of multi-carbon fatty acids from carbon dioxide - Chenjia Miao; Xiaoman He; Chen Deng; Bing Song; Alec Foster; Yang Yu; Dekui Shen; Richen Lin (Bioresource Technology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Non-Equilibrium Recovery of Plankton Communities in the Yangtze River Estuary: Three Years After the Fishing Ban - Bangping Deng; Wei Liu; Qiliang Song; Yuchen Guo; Chenxing Yang; Lin Zhu; Jun Li; Lijia Liu; Yin Yang; Xiucheng Yu (Fishes, 2026)
Large-scale fishing bans are increasingly implemented to restore aquatic ecosystems, yet their effects on lower trophic levels remain poorly understood. As one of the world’s largest estuarine systems, the Yangtze River Estuary has been subjected to a ten-year fishing ban since 2021, providing a unique opportunity to potentially examine the response of plankton community to reduced fishing pressure along a steep salinity–nutrient gradient. This study relies on one-off environmental and plankton field surveys conducted in autumn 2024 (a sampling instead of multi-year time-series monitoring), we applied redundancy analysis, Mantel tests, and threshold indicator taxa analysis to tentatively clarify the roles of nutrients and salinity in structuring post-ban plankton communities. Species richness may have increased substantially compared with pre-ban levels, but community evenness declined and the dominance of Skeletonema costatum could have intensified, revealing a possible non-equilibrium recovery pattern. Zooplankton density increased substantially, which may not be fully consistent with the expectation under a simple top-down release scenario. Threshold analysis showed that S. costatum exhibited bidirectional responses to dissolved inorganic nitrogen and phosphate, with its positive response thresholds matching ambient nutrient concentrations in the inner estuary; this discrepancy is only a plausible inference since we lack direct measurements of fish predation and zooplankton grazing rates to verify causal trophic interactions. Our findings suggest that bottom-up forces driven by persistent eutrophication remain the dominant control on plankton community structure three years after the ban. From a watershed management perspective, our observational results provide a tentative implication that substantial reductions in nutrient loading might be required to mitigate unbalanced plankton community recovery; otherwise, the structural integrity of plankton assemblages could lag far behind the recovery of species richness under the current eutrophic background.

Shared inflammatory targets of phthalate plasticizers in MODS-related syndromes: An integrative network toxicology study with representative DEHP in vitro validation - Lin Song; Aifeng He; Wei Jiang; Ke Liu; Jingyi Ma; Jing Wang; Keran Shi; Jiangquan Yu; Ruiqiang Zheng (Toxicology and Applied Pharmacology, 2026)

Structuring urban carbon metabolism through cross-sectoral and cross-media linkages: Evidence from a high-density city - Yu Lin; Jiahao Shi; Yichen Dong; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Sustainable Cities and Society, 2026)

Parametric assessment of downstream aerodynamic response under coupled wake effects and platform motions in floating wind turbines - Gao Xiaoxia; Gong Xiaoyu; Song Jianwei; Zhang Huanqiang; Wang Yu; Zhao Fei; Zhu Xiaoxun; Lin Xiang (Ocean Engineering, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Gastric pH-induced liquid–liquid phase separation between lactoferrin and osteopontin protects against proteolysis and modulates intestinal uptake - Lan Liu; Chenming Lin; Meidan Zheng; Xinyue Tu; Yaming Yu; Zehan Song; Guoqiang Qi; Shanshan Li; Mingying Yang; Bo Lönnerdal; Yajun Shuai (Food Research International, 2026)

One-pot biocatalytic synthesis of structurally uniform β-1,3-glucan from renewable cellobiose via a thermostable GH161 phosphorylase in an in vitro biosystem - Guotao Mao; Junhan Lin; Zhe Li; Jin Yu; Ming Song; Miaoqian Wang; Hongsen Zhang; Hui Xie; Zengping Su; Hongge Chen; Andong Song (Food Chemistry, 2026)

Battery swapping mode analysis for shared e-bikes from a carbon perspective - Yonggang Shen; Chenhan Lin; Yancun Song; Qing Yu; Yongping Zhang (Environmental Impact Assessment Review, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A Modified FMEA Framework Incorporating Confidence-Enhanced Probabilistic Linguistic Modeling and Weighted Hypergraph Propagation for LNG Storage Tank Risk Assessment - Yang Yu; Jiandong Ma; Jianxing Yu; Peimin Li; Lin Song; Yuheng Yang; Zhenglong Yang (Journal of Marine Science and Engineering, 2026)
LNG storage tanks are essential facilities for large-scale storage and transportation of cryogenic energy. Because of the flammable, explosive, and ultra-low-temperature characteristics of liquefied natural gas, failures in such systems may result in serious consequences for operational safety and the surrounding environment. Effective identification and prioritization of potential failure modes are therefore crucial for safe operation. Failure mode and effects analysis (FMEA) has been widely applied in risk assessment, yet conventional FMEA methods still show limited capability in describing uncertain linguistic evaluation information, reflecting the reliability of expert judgments, and representing high-order coupling relationships among failure modes. To address these issues, this study develops a modified FMEA framework that integrates confidence-enhanced probabilistic linguistic modeling with weighted hypergraph propagation for LNG storage tank risk assessment. In the proposed framework, confidence-enhanced probabilistic linguistic term sets are employed to represent the fuzziness, probabilistic preference, and reliability differences contained in expert assessments. A confidence-adaptive scoring function is further constructed to strengthen the discrimination of risk quantification by capturing structural differences in probability distributions without introducing externally specified parameters. Meanwhile, the importance of risk factors is determined through a combined subjective–objective weighting strategy, and a weighted hypergraph propagation mechanism is established to characterize high-order structural associations among failure modes and to revise baseline risk levels through a node–hyperedge–node transmission process. A case study of a large LNG storage tank system in Tangshan, China, is carried out to examine the applicability and effectiveness of the proposed framework. The results demonstrate that the proposed method can effectively integrate complex expert evaluation information with structural coupling effects, while sensitivity and comparative analyses further confirm its robustness and suitability for failure risk prioritization in LNG storage tanks.

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Multi-sensor fusion for autonomous vertical docking in kilometer-scale deep-sea environments - Suohang Zhang; Lin Yu; Shipang Qian; Jiaxuan Song; Ziyang Wan; Ruiheng Liu; Lu Wang; Xinyu Fei; Canjun Yang; Yanhu Chen (Ocean Engineering, 2026)

Ferroelectric field gating-assisted thermoelectric energy conversion - Ji Young Park; Sun-Woo Kim; Byoungjin Yoon; Youngbo Shim; Do-Heon Kim; Seong Wook Cho; Jun Chen; Young Hun Jeong; Sangwoo Ryu; Hak Ki Yu; Zhong Lin Wang; Hyesung Park; et al. (Chemical Engineering Journal, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

Evaluating sustainable coastal management strategies following Spartina alterniflora eradication: Insights from typhoon-induced hydro-sedimentary responses - Lv Gong; Yang Hu; Yuanhao Song; Liangxun Pan; Lin Su; Xiaoyu Yu; Wenzhen Zhao; Ben Li; Xiuzhen Li (Ocean & Coastal Management, 2026)

Anomaly detection for LNG storage tanks with limited sensor data using WGAN-CADA and multi-branch probabilistic autoencoder - Yang Yu; Jiandong Ma; Jianxing Yu; Zihang Jin; Hanxu Tian; Yuheng Yang; Lin Song (Process Safety and Environmental Protection, 2026)

Tailoring properties of corn starch via active extrusion: Key role of feed moisture - Xiaoshuai Yu; Jiangkai Zeng; Jinjie Huo; Jinming Ma; Jiaqi Song; Lin Wang; Mohamed E. Hassan; Yixin Peng; Bo Bo; Zhigang Xiao; Yumin Duan (Journal of Food Engineering, 2026)

A new Rhizomucor miehei lipase immobilized on anhydride-hydrophobized amino supports: Optimization, characterization and application in preparing medium- and long-chain structured lipids - Yiyi Lin; Xiansi Gao; Zheling Zeng; Di Kuang; Kai Fang; Tianyi Song; Ping Yu; Deming Gong; Cheng Zeng; Xianghui Yan (Food Bioscience, 2026)

Electrochemical dehydrogenation of layered double hydroxide for high-capacity aqueous magnesium-ion batteries - Yuqing Wang; Jianming Meng; Peng Hei; Yulai Lin; Bo Li; Xiaopeng Lu; Xiaoqi Sun; Yu Song (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

Environmental PET-microplastic exposure and risk of non-alcoholic fatty liver disease: An integrated computational toxicology and multi-omics study - Yu Yuan; Chunli Lin; Tianyu Zhang; Chao Song; Yuewen Sun; Hongzhen Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Integrated electricity‒heat scheduling optimization strategy for biomass-PV-battery islanded microgrid with micro turbine in high-latitude regions - Gong Wang; Ke Dong; Yuanhua Song; Shengxian Cao; Liuming Gao; Mingli Yu; Hao Gan; Chuanjie Lin; Guichao Duan; Huijing Sun (Biomass and Bioenergy, 2026)

Experimental Study on Hydrodynamic Responses of Multi-Body Floating Systems Under Combined Wind, Wave, and Current Loads - Lin Song; Jianxing Yu; Hanxu Tian; Ruilong Gao; Jiandong Ma; Zihang Jin (Journal of Marine Science and Engineering, 2026)
As the development of the ocean extends to the deep and open seas, the application of multi-hull floating systems is becoming increasingly widespread, covering offshore oil and gas transfer and material replenishment operations. In multi-body floating systems, the hydrodynamic interactions between adjacent floating bodies significantly affect the overall motion response and load distribution. However, there is currently a lack of systematic experimental research on systems involving three or more units under the combined action of wind, waves, and currents. This study presents a 1:50 scale model experiment on a five-body offshore replenishment station, comprising a central transfer platform and four surrounding vessels. Absolute six-degree-of-freedom motions and relative displacements between the transfer platform and neighboring vessels were measured. The results indicate distinct differences among the units. The peripheral vessels have greater horizontal and yaw motions, while the central units are more restricted. The relative motions are substantially increased for beam and oblique wave conditions, implying increased interaction effects in the gaps between neighboring bodies. Moreover, the combined oblique environmental loading and asymmetric mooring stiffness result in increased global drift and yaw motions. These findings provide benchmark data for numerical validation and practical guidance for the design and operation of multi-body floating systems.

Dynamic cross-sector and media assessment of urban phosphorus metabolism: underlying mechanisms, environmental implications, and driving forces - Yichen Dong; Yu Lin; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Environment, Development and Sustainability, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Corrigendum to “Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction” [Desalination, 619 (2026) 119555] - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Oxygen vacancy engineered M0.5Ni0.5Fe2O4 for enhanced chemical looping combustion performance - Xinyu Li; Jianshuai Li; Lina Wang; Lei Liu; Yan Lin; Shenglong Teng; Yiwen Song; Dewang Zeng; Yu Qiu (Chemical Engineering Journal, 2026)

Corrigendum to “An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration” [Carbohydrate Polymers 327 (2024) 121666] - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2026)

Multi-model machine learning framework for prediction of greenhouse gas emissions during composting of organic solid waste - Jing He; Jing Tang; Zhonghao He; Qiqi Fu; Yi Li; Ci Song; Wei Huang; Jiajia Wang; Jiangfang Yu; Lin Tang (Bioresource Technology, 2026)

Gibberellic acid (GA) alleviates Al toxicity in rice (Oryza sativa) through a nitric oxide (NO) dependent pathway - Qi Jiang; Hao Yu Wang; Yong Qiang Gao; Ren Fang Shen; Yi Lin Xu; Qing Song Zheng; Xiao Fang Zhu (Planta, 2026)

Rapid microfluidic sample preparation for mass spectrometric analysis of wild-type and mutant BRAF protein - Yen-Heng Lin; Heng-Yun Chang; Chia-Chun Wu; Yung-Chin Hsiao; Ying-Hao Wen; Jau-Song Yu (Analytica Chimica Acta, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Strength and leaching characteristics of lead-zinc contaminated red clay stabilized by CO2-enhanced active MgO carbonation - Kaibin Chen; Yu Song; Yu Chen; Yewei Lai; Zhi Lin Kong (Journal of Environmental Chemical Engineering, 2026)

Water quality and biofilm growth in drinking water distribution systems with the low-dose sodium hypochlorite disinfection after ultrafiltration pretreatment - Yu Zhou; Kangbing Zou; Xiaokai Wang; Zhihong Wang; Wei Song; Xing Du; Dachao Lin (Journal of Environmental Sciences, 2026)

Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Flexible multi-parameter sensing platform using MoWS2-BP composite for environmental and physiological monitoring - Yu Qi; Long Yang; Zitong Kan; Qingqing Zhou; Biao Dong; Guodong Wei; Hongwei Song; Lin Xu (Chemical Engineering Journal, 2026)

A new fucosylated glucuronoxylomannan from the fruit bodies of Tremella aurantia: structural characterization and immunoenhancing activity on seasonal influenza mRNA vaccine - Jing Chen; Yuan Ma; Zhi-Min Rao; Song-Lin Jiang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Rice yield prediction in unseen years at field level with high-resolution gross primary productivity derived from Sentinel-2 imagery - Weiguo Yu; Yuan Xiong; Xingrong Li; Hengbiao Zheng; Chongya Jiang; Xia Yao; Yan Zhu; Weixing Cao; Lin Qiu; Lijuan Song; Tao Cheng (Remote Sensing of Environment, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Ecological presence and functional role of bacteriophages in fermented vegetables - Xia Lin; Chunhui Deng; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Ziwei Liang; Lei Liu; Yu Rao (Food Microbiology, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Dual aggregation steering in bulk-heterojunction via solvent engineering toward efficient and stable binary organic solar cells - Yijing Lin; Bing Zheng; Xingting Liu; Huizhen Xu; Liyang Yu; Ruipeng Li; Xin Song; Weiguo Zhu (Chemical Engineering Journal, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Precursorship between the Indian Ocean dipole and the following year ENSO in the CMIP6 simulations - Yue Zhong; Wenshi Lin; Dongliang Yuan; Tuantuan Zhang; Song Yang; Shuheng Lin; Wei Yu; Hanjie Fan (Climate Dynamics, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Cyclic responses of typical seabed materials in two offshore wind farms of China - Bo Han; Xinran Yu; Zhishuai Zhang; Genqiang Peng; Mingbao Lin; Song Dai (Marine Georesources & Geotechnology, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Interfacial adsorption mechanism of a novel sodium morpholine dithiocarbamate depressant in selective flotation separation from chalcopyrite and molybdenite - Song Zou; Yue Lin; Zhiqiang Huang; Xinyang Yu; Guichun He (Minerals Engineering, 2025)

Photocatalytic activation of peroxyacetic acid by MnFe₂O₄ for efficient caffeine degradation: Efficacy, mechanisms and reusability - Ying Yu; Gengwei Lin; Huilin Dai; Qingsong Li; Chao Huang; Yunbo Song (Journal of Environmental Chemical Engineering, 2025)

Effects of reductive soil disinfestation on remediating microplastic-polluted soils and restructuring microbial communities - Haoxue Liu; Lin Dong; Xinjie Wang; Yu Sun; Kunshuo Yang; Enqing Chen; Wenlong Song; Lei Zhang (Journal of Environmental Chemical Engineering, 2025)

Multi-omics analysis reveals PkNF-YA7a as a transcriptional activator that promotes glycerolipid biosynthesis in Pinus koraiensis seeds - Zeyu An; Yuxin Song; He Zhang; Xin Wang; Dongran Zheng; Peitian Yu; Yangxin Wang; Wenqian Hao; Lin Wu; Yang Zhang; Hailong Shen; Yuhua Li; et al. (Food Chemistry, 2025)

Tracing antibiotics in food through dual-mode ratiometric luminescence core-shell nanoparticles - Xin Gao; Qi Li; Hanxiang Wu; Srushti Gadiyaram; Hongli Wen; Abdur Raheem Aleem; Wei Song; Lin Yu; Deshmukh Abdul Hakeem (Food Chemistry, 2025)

Analysis of the mechanism of quality deterioration of egg yolk powder during storage from a multi-dimensional perspective - Yiding Yu; Jiahui Song; Jun Jiang; Songyi Lin (Food Chemistry, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

Enzymatic hydrolysis of cassava leaf proteins unlocks antioxidant and therapeutic peptides: Alcalase-derived bioactives target oxidative stress pathways - Jinquan Zhang; Yusi Fang; Zuoda Zhang; Houmei Yu; Liming Lin; Qinfei Wang; Zhenwen Zhang; Yong Song (Food Chemistry, 2025)

Combined non-volatile and volatile metabolite profiles and antioxidant activities reveal the enhancement of traditional “steaming and Sun-drying nine times” on the functional properties of jujube - Yu Liu; Lijuan Zhang; Haijiao Lin; Zengyi Song; Pu Xu; Liming Zhang; Binbin Wei (Food Chemistry, 2025)

Microplastic accumulation in endometrial cancer tissues and its metabolic impact - Chunlin Dong; Hongwen Xu; Bing Zhang; Yaying Lin; Jing Song; Jinjin Yu; Ding Ma (Environmental Pollution, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Product and mechanistic insights into the ozonolysis of Δ3-Carene - Xulian Song; Xiaoxiao Lin; Yu Xia; Ziji Ma; Liqin Jin; Weijun Zhang; Zhandong Wang; Christa Fittschen; Xiaofeng Tang (Atmospheric Environment, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

Ribociclib derivative Rib-CA suppresses breast cancer progression via p53-dependent apoptosis - Mengwei Song; Ying Zhou; Xudong Yu; Boyu Zhang; Sen Wang; Kadirya Asan; Zihao Yang; Haiyan Lin; Jian Wang; Xiaoxue Song; Yongyuan Jiang; Si Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Integrated core-shell structured dual-mode thermoresponsive optical-electrical sensing fiber for accurate temperature recognition and early fire warning - Hualing He; Jie Xu; Md Hasib Mia; Zhonghe Yu; Yuhang Wan; Qing Jiang; Xueru Qu; Jinru Liu; Lin Hou; Yueyue Song; Zhicai Yu (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

One-pot tailored synthesis of highly monodisperse β-1,3-glucan from sucrose driven by an in vitro self-assembled dual-enzyme system via spy chemistry - Guotao Mao; Ming Song; Jin Yu; Junhan Lin; Zhanhe Wang; Zengping Su; Hui Xie; Hongsen Zhang; Hongge Chen; Andong Song (Carbohydrate Polymers, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Fate and health implications of polycyclic aromatic hydrocarbons in a sustainable food waste recycling system using housefly maggots and Nile tilapia - Chao Zheng; Zhang Cheng; Zhi-Lin Chen; Yu Bon Man; Qiao Liu; Liu-Lan Zhao; Song Yang; Ming Hung Wong (Aquaculture, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Transcriptome analysis revealed that largemouth bass (Micropterus salmoides) may mobilize liver lipid metabolism to provide energy for adaptation to hypertonic stress - Xinxin Wang; Chaoyue Deng; Wenyan Lin; Huapeng Chen; Haoran Yu; Shukui Sun; Junlong Sun; Jian Luo; Feibiao Song (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

A three-dimensional Pt@Ti₃C₂Tₓ-based smart platform for discrimination of hydrated ammonia in multi‐scenario environmental monitoring - Qingqing Zhou; Chencheng Hu; Yu Qi; Xiaoyi Tan; Jiaqi Yang; Zitong Kan; Long Yang; Biao Dong; Zhiyong Chang; Hongwei Song; Lin Xu (Journal of Hazardous Materials, 2025)

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Interleukin-6-taregeted dual-drug nanoparticles enhance glioblastoma chemotherapy by facilitating blood-brain barrier penetration and alleviating cardiotoxicity - Zesheng Sun; Jialiang Lin; Yue Huang; Qianqian Liu; Xucheng Zhu; Yu Yang; Ya Wen; Chunbin Shao; Weiquan Liao; Yan Song; Sharon Prince; Yi Wang; et al. (Chemical Engineering Journal, 2025)

Polarization induced by electric field electro-physically strengthened the proton-coupled electron transfer to promote electrotrophic methanogenesis - Yanwei Liu; Lin Xiao; Zuli Pan; Ouru Zhan; Yabin Gong; Bo Song; Yifeng Shou; Qilin Yu; Yaobin Zhang (Chemical Engineering Journal, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Analysis of Changes in Fractional Vegetation Cover ( FVC ) and the Impacts of Various Drivers in Subtropical Ecological Civilization Areas of Southern China - Hanyue Song; Qiuyue Zhao; Jiqing Lin; Kunyong Yu; Jian Liu (Journal of Biogeography, 2025)
Aim The Pilot Area for Subtropical Ecological Civilization in Southern China has made significant strides in ecological conservation through ecological projects and forest rights reform. This study assesses FVC dynamics to evaluate the relative impacts of climate change and human activities on vegetation restoration, aiming to inform optimised management strategies. Location Fujian Province, China. Time Period 2000–2023. Major Taxa Studies Fractional vegetation cover (FVC). Methods We utilised the pixel dichotomy method to derive FVC from MODIS13A2 data (2000–2023) within the Google Earth Engine platform. To evaluate the impacts of climate change and human activities on vegetation restoration, we applied slope trend analysis in conjunction with the Mann‐Kendall mutation test. Results (1) From 2000 to 2023, Vegetation Restoration in Fujian Province exhibited pronounced spatial heterogeneity. Approximately 72.65% of the region exhibited an increasing trend in FVC , with over 80% of the study area maintaining moderate to high levels of vegetation cover. In contrast, the southeastern coastal areas showed slower gains. (2) Approximately 69.55% of the changes in vegetation cover were attributed to the combined influence of human activities and climate change, with human activities contributing more significantly to vegetation restoration than climate change (67.88% vs. 64.14%). (3) Within the 40%–100% contribution range, the proportion of areas where human activities predominantly influenced changes in FVC was higher than that influenced by climate change (69.89% vs. 51.12%). (4) Although the total area of forests, shrublands and grasslands in Fujian Province declined during this period, the overall increase in FVC underscores the effectiveness of ecological restoration programs such as the Grain for Green Initiative. These findings indicate that even under substantial human disturbances, well‐targeted and effectively implemented ecological policies can act as key drivers of vegetation recovery. Main Conclusions This study highlights that even under intense human disturbance, well‐targeted and robust ecological policies remain the primary driving force behind vegetation recovery in subtropical ecological civilisation pilot zones. It underscores the importance of integrating climate adaptation strategies with human interventions to achieve effective ecological management, offering valuable insights and replicable pathways for vegetation restoration in other ecologically sensitive regions.

Preparation of glycine-pectin complex and its application in drug delivery system - Jia-Yu Li; Meng-Yuan Zhang; Yue Chen; Yu-Qing Song; Chao-Lin Wang; Chen-Yu Zhang; Guo-Wei Yu (Natural Product Research, 2025)

Remote sensing assessment of urban vegetation's dust retention for mitigating atmospheric particulate pollution - Wei Yang; Yan Yu; Wenpeng Lin; Jia Song; Yue Sun; Yuxun Zhang; Wei Zhang; Yue Li (Urban Climate, 2025)

Break-off and stagnation of the subducting Nazca slab in the mantle transition zone beneath West-Central South America - Kailun Ba; Jianping Huang; Youqiang Yu; Jianguo Song; Sanzhong Li; Cong Shen; Lin Liu (Tectonophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Narrowband deep-blue polymer light-emitting diodes: Beneficial from the individual planar-conformational chain segment in hierarchically ordered nano-domain - Bin Liu; Jiangli Cai; Yingying Zheng; Yang Xu; Jinghao Yang; Wenyu Chen; Mengyuan Li; Ningning Yu; Mingjian Ni; Lubing Bai; Chongping Song; Lili Sun; et al. (Chemical Engineering Journal, 2025)

Neighborhood Energy Supply-Demand Coordinated Design (NES-CoD) in early design stage - Junkang Song; Shuangdui Wu; Zihan Zhang; Hanjie Zheng; Pingan Ni; Shenfei Yu; Songjun Li; Hongli Sun; Borong Lin (Sustainable Cities and Society, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Tuning pH to motivate chain reaction of iron release with extracellular polymeric substances formation for long lasting Fe0-driven autotrophic denitrification - Ling Xiong; Binxue Song; Xumeng Lin; Ying Wu; Jintao Yu; Xiaonuan Wang; Huahan Huang; Yimei Cheng; Qifan Zhou; Gang Xue (Journal of Environmental Management, 2025)

Associations of exposure to arsenic species and endogenous sex hormones with oral cancer: a hospital-based study in Southeastern China - Na Wang; Wenting Zhang; Haoyuan Song; Weihai Huang; Fa Chen; Fengqiong Liu; Yulan Lin; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (Environmental Pollution, 2025)

A novel catalytic ozonation mechanism of MIL-53(Fe70Ce30): Role of abundant oxygen vacancies and unsaturated metal centers generated via Ce-doping - Hui Yu; Xiaochuan Lin; Shuxin Ren; Kaiyang Chen; Quan Sun; Min Song; Chaoqun Tan (Chemical Engineering Journal, 2025)

Polyhalogenated heterocycle additive induced in-situ 3D gelatinous polymerization with polysulfides for shuttle effect inhibited lithium-sulfur batteries - Xingkai Ma; Xinmei Song; Yaoda Wang; Junchuan Liang; Tianyu Shen; Zuoao Wu; Lina Qin; Huan Li; Tianchen Yu; Huaizhu Wang; Zuoxiu Tie; Yichao Yan; et al. (Chemical Engineering Journal, 2025)

Long-term characteristics of formaldehyde concentrations in four Chinese residences and estimation of annual average - Jin Ye; Zhiyuan Wang; Tao Yu; Wenbin Zhuang; Wenqing Lai; Lei Tian; Wenjun Leng; Ying Song; Shaodan Huang; Yinping Zhang; Cong Liu; Bencheng Lin (Building and Environment, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

Current research on the regulation of glycolipid metabolism by plant-derived active polysaccharides - Jiaxiang Xu; Zebin Weng; Qi Cui; Wen Yu; Yajuan Lin; Haizhao Song; Ling Xiong; Luanfeng Wang; Xinchun Shen; Fang Wang (Trends in Food Science & Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Efficient removal of tetracycline under neutral pH using FeOCl-modified carbon-based catalytic membrane via in-situ coupling fenton oxidation - Zonglin Pan; Xinyuan Zhou; Xinyu Liu; Chengwen Song; Wei Qian; Hang Yu; Ruisong Xu; Lin Li; Shuaifei Zhao; Tonghua Wang (Journal of Water Process Engineering, 2025)

Integration of volatile and nonvolatile metabolite profiles, and PPO activity reveals the methyl jasmonate protective advantage and metabolite characteristics of Houttuynia cordata during storage - Zengyi Song; Haijiao Lin; Yu Liu; Hongxi Zhang; Binbin Wei; Min Gu (Food Chemistry, 2025)

Tunning “closed-loop” pockets for constructing stabilized structures of nanobody in the detection of procymidone under a broad range of pH value - Hui-Wei Huang; Aori Qileng; Lin Luo; Yu Wang; Song Huang; Yu-Dong Shen; Min-Ling Liu; Zhen-Lin Xu (Food Chemistry, 2025)

Assessment of health risk and identification of pollution sources of heavy metals in water in Chongqing's wastewater treatment plants based on ICP-MS - Yaxuan Li; Jingqing Zhang; Nanchuan Song; Yiwu Wang; Jialing Yu; Lin He; Ruijia Yang; Lin Yang; Dan He (Environmental Pollution, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Island-like FeS2@TiO2 heterojunction modified separator for enhanced polysulfide management in lithium-sulfur batteries - Jing Song; Luchao Yue; Yifan Dou; Kun Yang; Lixin Zhang; Lin Jiang; Hongrui Liang; Yu Cao; Tianwei Fan; Xujie Zhang; Guisheng Qi; Xuping Sun; et al. (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Facile preparation of isolation columns filled with integral hybrid materials for efficient isolation of extracellular vesicles from microliter sample - Yujie Lin; Mengxi Chen; Yuanyuan Yu; Pengfei Xu; Fengyu Chen; Shenyue Zhou; Jiayu Xu; Wen Wu; Song Zhu; Yuxin An; Haiyang Zhang; Weipeng Wang (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

Mitigation pathways of urban heat islands and simulation of their effectiveness from a perspective of connectivity - Qiuyue Zhao; Ling Tao; Hanyue Song; Yuhang Lin; Yuejiao Ji; Jianwei Geng; Kunyong Yu; Jian Liu (Sustainable Cities and Society, 2025)

Spatially explicit land use of manufacturing sectors and its biodiversity impacts in China - Yutao Wang; Zhixiu Han; Yiru Song; Chen Sun; Lin Sun; Huajun Yu (Resources, Conservation and Recycling, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Waste to wealth: Waste liquid promotes rice growth in soda saline-alkali soil by improving Desulfocapsaceae abundance - Jianfeng Zhang; Xianfeng Lin; Xiaoyu Lin; Xu Song; Yu Wu; Fengyuan Jin; Hanchi Wang; Jing Liang; Jiejing Zhang (Journal of Environmental Chemical Engineering, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

How does globally accumulated tropical cyclone energy vary in response to a changing climate? - Kaiyue Shan; Fengfei Song; Yanluan Lin; Wenchao Chu; Chengfei He; Pao-Shin Chu; Lixin Wu; Xiping Yu (Science Bulletin, 2025)

MnOOH/carbon-based reactive electrochemical membrane for aqueous organic pollutants decontamination - Zonglin Pan; Chunyu Wang; Xinyu Liu; Ruisong Xu; Hong Xin; Hang Yu; Lin Li; Shuaifei Zhao; Chengwen Song; Tonghua Wang (Journal of Environmental Management, 2025)

Evaluating complementaries among urban water, energy, infrastructure, and social Sustainable Development Goals in China - Ke Yu; Yifan Song; Jin Lin; Shen Qu (Journal of Environmental Sciences, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Glioma stem cell membrane-camouflaged photothermal nanozyme for synergistic antitumor via dual-targeted drug delivery across blood-brain barrier - Jialiang Lin; Zesheng Sun; Yue Huang; Qianqian Liu; Mujie Shen; Chunbin Shao; Weiquan Liao; Yu Yang; Yan Song; Yi Wang; Rongqin Huang; Jinlong Shi (Chemical Engineering Journal, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A simple and efficient TALEN system for genome editing in plants - Qing Liu; Lizhou Lin; Shengjian He; Jianghui Yu; Caili Xie; Chaoyue Gai; Yongqiang Han; Chunmei Liu; Feihan Huang; Daoqian Chen; Yuanyuan Song; Guannan Qin; et al. (Plant Molecular Biology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Sensitive Fluorescent Probe for Al3+, Cr3+ and Fe3+: Application in Real Water Samples and Logic Gate - Ziyun Lin; Yu Shi; Yanxi Song; Jiabao Yan; Hongqi Li; Chengxiao Xie (Journal of Fluorescence, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Characteristic analysis and diagnosis method optimization of scroll compressor pressure pulsation signal under voltage fluctuation - Yanjie Zhao; Tonghe Zhang; Yongxing Song; Qiang Liu; Lin Liu; Ming Yu; Yi Ge (International Journal of Refrigeration, 2025)

Effect of hot-air drying processing on the volatile organic compounds and maillard precursors of Dictyophora Rubrovalvata based on GC-IMS, HPLC and LC-MS - Lingshuai Meng; Yu Nie; Qingsong Zhou; Tingting Zheng; Jianxin Song; Chao Zhang; Haijiang Chen; Dong Lin; Sen Cao; Su Xu (Food Chemistry, 2025)

Synergy between single atom and nanoclusters promotes power and CO tolerant performance in PEMFCs - Jiwen Lin; Zhongyao Zhang; Jiaye Qiu; Yujie Wu; Jun Yu; Yongliang Li; Xiangzhong Ren; Lei Zhang; Zhongxin Song (Chemical Engineering Journal, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Study on the resilience recovery of civil airport infrastructure under weather extremes - Xin Huang; Lizhi Yang; Kun Wu; Cheng-song Tan; Lin Qi; Yu Chen (Natural Hazards, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Random Forest-Based Prediction Model for Stiffness Degradation of Offshore Wind Farm Submarine Soil - Ben He; Mingbao Lin; Xinran Yu; Zhishuai Zhang; Song Dai (Journal of Marine Science and Engineering, 2024)
Offshore wind power is a hot spot in the field of new energy, with foundation construction costs representing approximately 30% of the total investment in wind farm construction. Offshore wind turbines are subjected to long-term cyclic loads, and seabed materials are prone to causing stiffness degradation. The accurate disclosure of the mechanical properties of marine soil is critical to the safety and stability of the foundation structure of offshore wind turbines. The stiffness degradation laws of mucky clay and silt clay from offshore wind turbines were firstly investigated in the study. Experiments found that the variations in the elastic modulus presented “L-type” attenuation under small cyclic loads, and the degradation coefficient fleetingly decayed to the strength progressive line under large cyclic loads. Based on the experimental results, a random forest prediction model for the elastic modulus of the submarine soil was established, which had high prediction accuracy. The influence of testing the loading parameters of the submarine soil on the prediction results was greater than that of the soil’s physical property parameters. In criticality, the CSR had the greatest impact on the prediction results. This study provides a more efficient method for the stiffness degradation assessment of submarine soil materials in offshore wind farms.

Failure criterion of submarine completely weathered granite under cyclic loads in rock-based sea area - Song Dai; Xinran Yu; Bo Han; Zhishuang Zhang; Ben He; Mingbao Lin (Ocean Engineering, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Alpha-ketoglutarate supramolecular network accelerates diabetic wound healing through exudates management and neovascularization - Yimeng Cai; Pochun Lin; Yuhan Li; Linfeng Liu; Shuqin Cao; Bin Zhao; Yueying Wang; Wei Song; Qian Wang; Xinyan Gan; Ke Xu; Qingheng Wu; et al. (Chemical Engineering Journal, 2024)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Arsenic-contaminated soil remediation with hyperthermophilic compost: Effects on arsenic bioavailability, soil fertility and bacterial community - Liu Yang; Yingle Chen; Song Wang; Shu Lin; Guowen Huang; Zhihong Wang; Zhen Yu; Lei Zeng (Journal of Environmental Management, 2024)

Capacitive and biocompatibility composite anode material for enhanced renewable energy conversion for MFCs - Yuyang Wang; Zhijie Wang; Xiangquan Kong; Yu Song; Ye Tian; Jing Lin (Fuel, 2024)

Creating smart chlorine-resistant polyamide reverse osmosis membranes via self-healing temperature-responsive nanocontainer functionalization - Qian Yang; Lin Zhang; Yanzhuang Jiang; Song Xu; Beili Pang; Qiong Sun; Na Song; Jianguang Feng; Liyan Yu; Lifeng Dong (Chemical Engineering Journal, 2024)

An unsaturated chain carbonate additive contributing to high-performance LiFePO4//graphite battery at broad temperature range - Xin-Lin Zhang; Bin Dong; Yi Jin; Jia-Shun Song; Li Li; Jia-Yu Wang; Yu-Ying Zhu; Yan-Yun Sun (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

The nexus of solar absorption and morphology designs based on 2D photothermal materials: From rational design to advanced application of water purification - Tingting Jiang; Sihui Bian; Yu Wang; Xiaorui Fan; Lin Zhu; Xinyue Song; Guanbo wang; Tianhao Wang; Haifeng Zhang (Chemical Engineering Journal, 2024)

Development of Ce-doped NH2-UiO-66(Zr) photocatalysts for efficient CO2 reduction in an aqueous system - Chao Yu; Xianjin Zhang; Chenxu Song; Yanna Wang; Jing Lin; Zhonglu Guo; Yujie Zhang; Zhenya Liu; Chunsheng Li; Yan Sun; Chengchun Tang; Yang Huang (Chemical Engineering Journal, 2024)

Selective and Sensitive Detection of Hg2+ and Ag+ by a Fluorescent and Colorimetric Probe with Large Stokes Shift - Hongqi Li; Jiabao Yan; Lin Jiang; Yong Zhao; Yanxi Song; Jirui Yu; Lang Cheng (Journal of Fluorescence, 2024)

Bearing Behavior of Large-Diameter Monopile Foundations of Offshore Wind Turbines in Weathered Residual Soil Seabeds - Ben He; Mingbao Lin; Xinran Yu; Genqiang Peng; Guoxiang Huang; Song Dai (Journal of Marine Science and Engineering, 2024)
The southeastern rock base sea area is the most abundant wind resource area, and it is also the mainstream construction site of offshore wind farms (OWFs) in China. The weathered residual soil is the main seabed component in the rock base area, which is the important bearing stratum of the offshore wind turbine foundation. Previous studies on the mechanical properties of seabed materials and bearing characteristics of the pile foundations in OWFs have mainly focused on the submarine soil-based seabed, resulting in a lack of direct reference for the construction of offshore wind power in the rocky seabed. Therefore, the mechanical properties of weathered residual soil and the bearing behaviors of monopile foundations are mainly investigated in this study. Firstly, dynamic triaxial tests are conducted on the weathered residual soil, and experiments analyze insight into the evolution law of the hysteresis curve, cumulative strain, and stiffness attenuation. Then, the horizontal loading behaviors of monopile foundations in residual soil are analyzed by numerical simulations; more critically, the service performances under wind and wave coupling loads are evaluated, which provide a direct theoretical basis for the construction and design of offshore wind turbine foundations in rock base seabeds.

An extended investigation on allele frequency of resistance to Bt maize in the southwestern corn borer and sugarcane borer (Lepidoptera: Crambidae) in the mid-south region of the United States - Fangneng Huang; Ying Niu; Qisheng Song; Scott Stewart; Blake Wilson; Graham Head; Sebe Brown; Wenbo Yu; Tiago Silva; Caroline Sakuno; Shucong Lin (Crop Protection, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Complete chromium removal via photocatalytic reduction and adsorption using bimetallic UiO-66(Zr/Al) - Chao Yu; Chenxu Song; Xianjin Zhang; Yanna Wang; Jing Lin; Yang Huang; Zhonglu Guo; Chunsheng Li; Yujie Zhang; Zhenya Liu; Chengchun Tang; Yan Sun (Journal of Environmental Chemical Engineering, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

Comparison of in vivo glycolipid metabolism regulation pathway of lotus leaf polysaccharide and its combination with flavonoids and alkaloids: Effectiveness of high-pressure homogenization-assisted dual enzyme extraction - Yaxin Song; Yu Ke; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Assessment of the antimicrobial and immunomodulatory activity of QS-CATH, a promising therapeutic agent isolated from the Chinese spiny frogs (Quasipaa spinosa) - Wei-Cheng Zheng; Xiao-Yun Cheng; Yu-Hui Tao; Yue-Song Mao; Cheng-Pu Lu; Zhi-Hua Lin; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

The changes and the potential clinical applications of cytokines in Taiwan’s major venomous snakebites patients - Chih-Chuan Lin; Chia-Cheng Wang; Chun-Hsiang Ou Yang; Chien-Chun Liu; Jau-Song Yu; Wen-Chih Fann; Yen-Chia Chen; Chia-Pang Shih (Toxicon, 2024)

Positive contributions of the stem to the formation of white tea quality-related metabolites during withering - Lihui Xiang; Chen Zhu; Jiajia Qian; Xiaochen Zhou; Miao Wang; Zhenshuo Song; Changsong Chen; Wenquan Yu; Lin Chen; Lanting Zeng (Food Chemistry, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

Exploration of Positive and Negative Schizophrenia Symptom Heterogeneity and Establishment of Symptom-Related miRNA-mRNA Regulatory Network: Based on Transcriptome Sequencing Data - Mengdi Jin; Mengtong Xie; Lin Dong; Fengyu Xue; Weizhen Li; Lintong Jiang; Junnan Li; Min Zhang; Haideng Song; Qingxing Lu; Qiong Yu (Molecular Neurobiology, 2024)

A temperature compensated fiber probe for highly sensitive detection in virus gene biosensing - Xiaopeng Han; Yu Zhang; Yundong Zhang; Qinghao Song; Wuliji Hasi; Siyu Lin; Fan Wang (Analytica Chimica Acta, 2024)

IFNγ modulates the innate immune response via Toll-like receptors in green-spotted pufferfish (Tetraodon nigroviridis) - Wenjie Lai; Qinxi Dai; Zhenjiang Zou; Ziyi Wu; Ting Wang; Xue Yu; Yakang Song; Jingpeng Hou; Yuyou Lu; Dingrui Liu; Haoran Lin; Yong Zhang; et al. (Aquaculture International, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Berberine hydrochloride delays citrus sour rot mainly by disrupting carbohydrate and energy metabolism of Geotrichum citri-aurantii spores - Lu Li; Bo Lin; Yu Ting; Maohui Li; Jinjin Hu; Jingjing Song; Yingjuan Yan; Jiaxin Chen; Hong Xiao; Nengguo Tao (Pesticide Biochemistry and Physiology, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

A novel strategy for enhancing the stability of aptamer conformations in heavy metal ion detection - Shi Quan Qian; Min Yuan; Xian Wei Zuo; Hui Cao; Jin Song Yu; Li-Ling Hao; Kun Lin Yang; Fei Xu (Analytica Chimica Acta, 2024)

Deblurring Network for UV Images of Colorless Chemicals Floating on Sea Surface - Hui Huang; Yu Zhang; Chuansong Lin; Fuliang Lin; Yue Fang; Hong Song (Journal of Marine Science and Engineering, 2024)
Automatic imaging monitoring technology has been developed as a mature solution to address oil spill accidents. However, when airborne equipment is used to monitor the area of leakage, there is a chance of relative motion between the equipment and the target, leading to blurred images. This can hinder subsequent monitoring tasks, such as the identification and segmentation of hazardous chemical targets. Therefore, it is crucial to deblur these images, as sharper images can substantially improve the precision and accuracy of these tasks. In light of this, this paper presents a novel multi-scale recurrent deblurring network, leveraging the Convolutional Block Attention Module (CBAM) attention mechanism, to restore clear images in an end-to-end manner. The CBAM attention mechanism has been incorporated, which learns features in both the spatial and channel domains, thereby enhancing the deblurring ability of the network by combining the attention mechanisms of multiple domains. To evaluate the effectiveness of the proposed method, we applied the deblurring network to our self-built dataset of blurred ultraviolet (UV) images of colorless chemicals floating on water surfaces. Compared to the SRN-Deblur deblurring network, the proposed approach yields improved PSNR and SSIM results. Moreover, when compared with the state-of-the-art DeblurGANv2 method, it performs better in the SSIM. These results demonstrate that the proposed multi-scale recurrent deblurring network, based on the CBAM attention mechanism, exhibits a superior deblurring performance.

Comprehensive effects of microplastics on algae-laden surface water treatment by coagulation-ultrafiltration combined process: Algae cultivation, coagulation performance and membrane fouling development - Dachao Lin; Zhongjian Zhuang; Nan Yu; Zhihong Wang; Wei Song; Xing Du (Science of The Total Environment, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

A novel BACG inverse reliability algorithm for efficient and robust reliability-based topology optimization of marine structures - Yupeng Cui; Baolei Zhang; Yang Yu; Siyuan Cheng; Mingxiu Wei; Zihang Jin; Lin Song (Ocean Engineering, 2024)

Highly water-soluble and biocompatible hyaluronic acid functionalized upconversion nanoparticles as ratiometric nanoprobes for label-free detection of nitrofuran and doxorubicin - Abdur Raheem Aleem; Rihui Chen; Tonghua Wan; Wei Song; Chuyan Wu; Xue Qiu; Qiuqiang Zhan; Kuncheng Xu; Xin Gao; Tianci Dong; Xiang Chen; Lin Yu; et al. (Food Chemistry, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

An overview on the life cycle of lithium iron phosphate: synthesis, modification, application, and recycling - Tianyu Zhao; Harshit Mahandra; Rajashekhar Marthi; Xiaobo Ji; Wenqing Zhao; Sujin Chae; Michael Traversy; Weilun Li; Fan Yu; Lin Li; Yeonuk Choi; Ahmad Ghahreman; et al. (Chemical Engineering Journal, 2024)

A Pollution Barrier Self-Healing Material: Investigating the Effect of Individual Components on Its Performance and Determining Optimal Ratios and Healing Compositions - Fuhao Fan; Haibo Li; Liuyu Song; Ying Lin; Xiaofei Qin; Yang Liu; Sihan Li; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

Effect of static magnetic field-assisted thawing on the quality, water status, and myofibrillar protein characteristics of frozen beef steaks - Wenxin Wang; Hengxun Lin; Wenqiang Guan; Yu Song; Xingxing He; Dequan Zhang (Food Chemistry, 2024)

Enhanced electrooxidation/electrocoagulation-ultrafiltration membrane process with S2O42− for saline algae-containing surface water treatment: Purification and membrane performance - Wei Song; Bingxuan Li; Zhongjian Zhuang; Xing Du; Dachao Lin; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Antifouling and antibacterial bioactive metabolites of marine fungus (terrein)/polyamide thin-film composite reverse osmosis membranes for desalination applications - Lin Zhang; Qian Yang; Yanzhuang Jiang; Liyan Yu; Na Song; Donglin Zhao; Lina Sui; Lifeng Dong (Desalination, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2024)

Metagenomic insights into protein degradation mechanisms in natural fermentation of cassava leaves - Jinquan Zhang; Qinfei Wang; Houmei Yu; Liming Lin; Zhenwen Zhang; Yong Song (Bioresource Technology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Can public opinion persuade the government to strengthen the use of environmental regulation policy tools? Evidence from policy texts - Song Chai; Mengxian Wei; Lin Tang; Xintian Bi; Yawen Yu; Jin Yang; Zhu Jie (Journal of Cleaner Production, 2024)

Mineralogy and geochemistry of magnetite in the Zhdanov Ni-Cu-(PGE) deposit in the Pechenga ore field, Russia: Implications for the formation of magmatic sulfide ores - Qing-Lin Liang; Xie-Yan Song; Valery Smolkin; Nadezhda A. Krivolutskaya; Song-Yue Yu; Lie-Meng Chen (Journal of Asian Earth Sciences, 2024)

A confined self-assembly approach towards chiral photonic materials with circularly polarized structural colors for information storage and encryption - Lin-Yue Li; Dong Li; Xiu Dong; Qiang-Wu Tan; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Molecular compositions of marine organic aerosols over the Bohai and Yellow Seas: Influence of primary emission and secondary formation - Fang Cao; Yi-Xuan Zhang; Yan-Lin Zhang; Wen-Huai Song; Yu-Xian Zhang; Yu-Chi Lin; Chaman Gul; Md. Mozammel Haque (Atmospheric Research, 2024)

The response of rhubarb to smut infection is revealed through a comparative transcriptome and metabolome study - Shuangshuang Zhou; Ya Lin; Yu Cai; Linfang Li; Xiaohui Yao; Kuan Sun; Qin Song; Qingwei Zhang (Planta, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Binary-1D/2D nanomaterial-functionalization toward strong, stretchable, and anti-freezing electrically conductive organohydrogels for self-powered operation monitoring of robotic hand - Jie Zhou; Bo Tang; Dong Li; Cheng-Wei You; Yu-Yao Zhao; Lin-Yue Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Polysaccharide from walnut green husk alleviates liver inflammation and gluconeogenesis dysfunction by altering gut microbiota in ochratoxin A-induced mice - Yang Yang; Linjie Lv; Shanshan Shi; Gaofeng Cai; Lin Yu; Shuwen Xu; Tianyu Zhu; Xinyue Su; Ningning Mao; Yue Zhang; Song Peng; Jin He; et al. (Carbohydrate Polymers, 2023)

Recalcitrant organic carbon plays a key role in soil carbon sequestration along a long-term vegetation succession on the Loess Plateau - Jingwei Shi; Mingyang Song; Lin Yang; Fei Zhao; Jianzhao Wu; Jiwei Li; Zhijing Yu; Ao Li; Zhouping Shangguan; Lei Deng (CATENA, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Zero-valent iron-peroxydisulfate as synergistic co-milling agents for enhanced mechanochemical destruction of 2,4-dichlorophenol: Coupling reduction with oxidation - Ludi Song; Lvren Lin; Wenjia Wei; Shengkun Zhang; Lei Wan; Zimo Lou; Jianming Yu; Xinhua Xu (Journal of Environmental Management, 2023)

Response of topsoil Fe-bound organic carbon pool and microbial community to Spartina alterniflora invasion in coastal wetlands - Meifen Lin; Yu Chen; Liwen Cheng; Yi Zheng; Weiqi Wang; Jordi Sardans; Zhaoliang Song; Georg Guggenberger; Yuanchun Zou; Xueli Ding; Akash Tariq; Fanjiang Zeng; et al. (CATENA, 2023)

Effects of the core heading date genes Hd1, Ghd7, DTH8, and PRR37 on yield-related traits in rice - Kangli Sun; Wubei Zong; Dongdong Xiao; Zeqiang Wu; Xiaotong Guo; Fuquan Li; Yingang Song; Shengting Li; Guangliang Wei; Yu Hao; Bingqun Xu; Weitao Li; et al. (Theoretical and Applied Genetics, 2023)

Large-diameter trees buffer monsoonal changes to tree biomass over two decades - Chen-Chia Ku; Jianwu Tang; Wei-Chun Chao; Kuo-Jung Chao; Guo-Zhang Michael Song; Huan-Yu Lin; James A. Lutz (Plant Ecology, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Short-term PM2.5 exposure induces transient lung injury and repair - Yu Li; Bencheng Lin; De Hao; Zhongchao Du; Qi Wang; Zhaoyu Song; Xue Li; Kuan Li; Jianhai Wang; Qiuyang Zhang; Junping Wu; Zhuge Xi; et al. (Journal of Hazardous Materials, 2023)

The shear resistance mechanism of prestressed anchor cables in slope reinforcement - Xiao-Gang Wang; Yu-Fei Zhao; Yong Nie; Xing-Chao Lin; Xing-Song Sun (International Journal of Rock Mechanics and Mining Sciences, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

The immune enhancement effect of CpG-ODNs on the vaccine of inactivated Vibrio harveyi in tiger puffer (Takifugu rubripes) - Simiao Yu; Lei Gao; Zhen Geng; Wei Wu; Xuejie Lin; Ruijun Li; Shigen Ye; Lingling Wang; Linsheng Song (Aquaculture, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Decorating {0 0 1} TiO2 nanosheets on hydrophobic NaY zeolite: An efficient deactivation-resistant photocatalyst for gaseous toluene removal - Juntao Tang; Mengying Fu; Yidan Mao; Shuyi Yang; Wei Lin; Yan Yu; Shuang Song (Chemical Engineering Journal, 2023)

Tanshinone IIA (TSIIA) represses the progression of non-small cell lung cancer by the circ_0020123/miR-1299/HMGB3 pathway - Fei Sun; Xiaoli Yang; Wei Song; Nan Yu; Qingyi Lin (Molecular and Cellular Biochemistry, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Daphnane-type diterpenoids from Stellera chamaejasme L. and their inhibitory activity against hepatocellular carcinoma cells - Zhuo-Yang Cheng; Jing-Xian Ren; Xiao-Bian Xue; Man Wang; Xiao-Qi Yu; Bin Lin; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Hierarchical CoMn-LDH based photothermal membrane with low evaporation enthalpy and narrow bandgap toward highly efficient Solar-Driven evaporation - Ruoxuan Zheng; Tong Lin; Wan-Lei Zhao; Rutao Yin; Hongqiang Li; Zhuoqun Deng; Wei Chen; Yu-Fei Song (Chemical Engineering Journal, 2023)

Drug-free and non-crosslinked chitosan/hyaluronic acid hybrid hydrogel for synergistic healing of infected diabetic wounds - Yao Lin; Jingchen Xu; Yuanhao Dong; Yue Wang; Chenhao Yu; Yuanhong Li; Chaoliang Zhang; Qianming Chen; Song Chen; Qiang Peng (Carbohydrate Polymers, 2023)

Food aflatoxin exposure assessment in Sichuan Province, China - Bi Zhao; Yi Xu; Yang Song; Yu Zhang; Li Lin (Mycotoxin Research, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Priming effects of nZVI on carbon sequestration and iron uptake are positively mediated by AM fungus in semiarid agricultural soils - Yu-Miao Yang; Minha Naseer; Ying Zhu; Bao-Zhong Wang; Song Wang; Yue Ma; Xiao-Lin Zhang; Xu-Zhe Zhao; Wen-Ying Wang; Shuang-Guo Zhu; Hong-Yan Tao; You-Cai Xiong (Science of The Total Environment, 2023)

Engineering highly efficient NIR-II FRET platform for Background-Free homogeneous detection of SARS-CoV-2 neutralizing antibodies in whole blood - Lei Zhao; Qingwei Song; Weikang Mai; Min Deng; Yu Lei; Lu Chen; Weiya Kong; Lei Zhang; Lin Zhang; Yantao Li; Huiru Ye; Yiru Qin; et al. (Chemical Engineering Journal, 2023)

Establishment of a lipopolysaccharide-induced inflammation model of human fetal colon cells - Keqi Yu; Shengtao Liao; Chuanfei Li; Ya Song; Zhechuan Mei; Lin Lv (Molecular Biology Reports, 2023)

Potential ecological risks of heavy metals and Cd accumulation characteristics of Suaeda salsa under different Cd input and water logging conditions in the Yellow River estuary, China - Hongli Song; Lin Kuang; Lizhi Wang; Wanni Yu; Yuanzhi Wu; Juan An; Xiyuan Wu (Environmental Science and Pollution Research, 2023)

An Experimental Study on the Resistance of a High-Speed Air Cavity Craft - Lin Song; Jianxing Yu; Yang Yu; Zhaoyu Wang; Shibo Wu; Ruilong Gao (Journal of Marine Science and Engineering, 2023)
For the marine industry, resistance reduction can reduce energy consumption and achieve protection of the marine environment. The use of air lubrication to reduce the resistance of ships is one of the most important ways. With this technology, high-speed air cavity crafts show immense potential as they can be utilized in various marine activities, such as emergency rescue, supply, and maritime security. Through experiments, this study presents an in-depth analysis of the effects of bubble chamber pressure and initial stern inclination on the resistance of high-speed air cavity crafts at different speeds. The results show that air pressure has a significant impact on resistance. It was found that as the speed of the ship increased, the resistance reduction effect became more prominent under the same pressure conditions. Moreover, the resistance tended to stabilize when the pressure reached a certain value. In addition to the air pressure, the longitudinal inclination does have an effect on resistance reduction. To achieve better resistance reduction, the initial stern inclination angle should be chosen appropriately. Furthermore, adjusting the angle with speed changes can optimize the resistance reduction effect. This experimental study provides critical support for conducting further research on high-speed air cavity crafts. The findings offer valuable insights into improving hull forms, guiding host selection, and assessing performance.

Mycotoxin deoxynivalenol-induced intestinal flora disorders, dysfunction and organ damage in broilers and pigs - Bingxuan Jia; Huikang Lin; Song Yu; Na Liu; Dianzhen Yu; Aibo Wu (Journal of Hazardous Materials, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Cartilage-targeting mRNA-lipid nanoparticles rescue perifocal apoptotic chondrocytes for integrative cartilage repair - Xinning Yu; Tengjing Xu; Huimin Shi; Jianqiao Hong; Xiaoqiang Jin; Le Cao; Jiajie Wang; Yunting Lin; Zongyou Pan; Siheng Wang; Jinghua Fang; Kaiwang Xu; et al. (Chemical Engineering Journal, 2023)

Linking peptide-oriented surface imprinting magnetic nanoparticle with carbon nanotube-based fluorescence signal output device for ultrasensitive detection of glycoprotein - Shi-Song Yu; Yu-Jun Shi; Di Wang; Ti-Ti Qiang; Ya-Qi Zhao; Xin-Yu Wang; Jia-Meng Zhao; Lin-Yi Dong; Ya-Jie Huang; Xian-Hua Wang (Analytica Chimica Acta, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Selective accumulation of ionic nanocrystal H2 storage system as an in situ H2/boric acid nanogenerator fights against ethanol-induced gastric ulcers - Chih-Wei Chou; Wei-Tso Chia; Cam-Hoa Mac; Cheng-Yu Wu; Chun-Chieh Chen; Hsiang-Lin Song; Yi-Hsuan Lin; Yu-Jung Lin; Hsing-Wen Sung (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Emulsifier free fish gelatin based films with excellent antioxidative and antibacterial activity: Preparation, characterization and application in coating preservation of fish fillets - Gaojie Song; Sheng Lin; Yuesheng Wu; Jiaping Shen; Jiulin Wu; Wenjin Zhu; Shuna Yu; Jianhua Li; Shaoyun Wang (Journal of Food Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

Sonocatalytic removal of tetracycline in the presence of S-scheme Cu2O/BiFeO3 heterojunction: Operating parameters, mechanisms, degradation pathways and toxicological evaluation - Xin Wang; Xue-Song He; Chun-Yu Li; Shi-Lin Liu; Wen Lu; Zheng Xiang; Yang Wang (Journal of Water Process Engineering, 2023)

Marangoni-driven biomimetic salt secretion evaporator - Yu Chen; Jin Yang; Lin Zhu; Sizhe Wang; Xiaohua Jia; Yong Li; Dan Shao; Lei Feng; Haojie Song (Desalination, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Gastropod chemoreception behaviors—Mechanisms underlying the perception and location of targets and implications for shellfish fishery development in aquatic environments - Zheng-Lin Yu; Mei-Jie Yang; Hao Song; Tao Zhang; Xiu-Tang Yuan (Frontiers in Marine Science, 2023)
Chemoreception is one of the most important senses and it plays a key role in the survival and adaptation of animals to their environments. Many gastropods, such as Rapana venosa and Neptunea cumingii , have emerged as economically important shellfish. Meanwhile, invasive gastropods have destroyed commercial shellfisheries in many countries. Given the importance of chemoreception in the behavior of aquatic gastropods, the mechanism of their chemical perception has recently garnered attention. To provide a foundation for understanding the chemoreception of aquatic gastropods, we reviewed recent studies and summarized the chemoreception behaviors and mechanisms that gastropods use to perceive and locate targets in aquatic environments, along with relevant molecular and genetic insights. We highlight several of the implications of these studies for chemoreception-related research and shellfish fishery development. This review should aid in the rational development and utilization of gastropod resources as well as in controlling the populations of invasive species.

The onset process of the 2018/2019 Indonesian–Australian summer monsoon: The importance of the air–sea interaction - Yongliang Duan; Hongwei Liu; Ming Feng; Xiangzhou Song; Kuiping Li; Lin Liu; Baochao Liu; Guang Yang; Weidong Yu (Frontiers in Marine Science, 2023)
The Madden–Julian oscillation (MJO) and its associated air–sea interactions during the onset process of the 2018/2019 Indonesian–Australian summer monsoon (IASM) are investigated based on the in situ data from a moored buoy off the coast of northwest Australia, along with ERA5 reanalysis and satellite data. The results verify that the IASM onset in mid-December 2018 was triggered by the first-branch eastward-propagating MJO (FEMJO) originating from the tropical Indian Ocean. However, the strong negative SST anomaly (SSTA) was evident off northwest Australia, which weakens FEMJO over northern Australia and shifts the convective center further northward. The mixed layer heat budget analysis based on the buoy observations reveals that the increased latent heat loss that occurred before the arrival of the FEMJO convection was primarily attributed to the large air–sea temperature difference and strong winds, resulting in the pronounced SSTA.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Residential greenness and dyslipidemia risk: Dose-response relations and mediation through BMI and air pollution - Qinjian Wang; Xiaoqing Li; Wenling Zhong; Hongyun Liu; Chuanteng Feng; Chao Song; Bin Yu; Yao Fu; Xi Lin; Yanrong Yin; Tiehui Chen; Jan D. Reinhardt; et al. (Environmental Research, 2023)

Activated peroxydisulfate by sorghum straw-based biochar for enhanced tartrazine degradation: Roles of adsorption and radical/nonradical processes - Xiaojuan Chen; Yu Zhou; Jiesen Li; Suresh C. Pillai; Nanthi Bolan; Juhua He; Ning Li; Song Xu; Xin Chen; Qinghua Lin; Hailong Wang (Environmental Pollution, 2023)

Recycle waste washcloth to design Fe3O4/FeS2/C heterojunction membrane as high-area capacity freestanding anode for sodium-ion batteries - Qing Lin; Shaocheng Zhang; Li-Juan Yu; Baoxiu Hou; Shuaihua Zhang; Zheng Wang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Aluminum/lead tetroxide nanothermites for semiconductor bridge applications - Chunpei Yu; Zilong Zheng; Bonan Gu; Yajie Chen; Jianyong Xu; Lin Zhang; Wei Shi; Jiaxin Wang; Changkun Song; Junhong Chen; Kefeng Ma; Wenchao Zhang (Chemical Engineering Journal, 2023)

Quantification of fossil and non-fossil sources to the reduction of carbonaceous aerosols in the Yangtze River Delta, China: Insights from radiocarbon analysis during 2014–2019 - Mingyuan Yu; Yan-Lin Zhang; Tian Xie; Wenhuai Song; Yu-Chi Lin; Yuxian Zhang; Fang Cao; Chi Yang; Sӧnke Szidat (Atmospheric Environment, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

RNAseq-based transcriptome analysis of lettuce infected by the necrotrophic fungus Sclerotinia Sclerotiorum - Liguang Tang; Bincai Wang; Liping Song; Chuying Yu; Chufa Lin; Changbin Gao; Daohong Jiang; Aihua Wang (European Journal of Plant Pathology, 2023)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Locus-level antagonistic selection shaped the polygenic architecture of human complex diseases - Weichen Song; Kai Yuan; Zhe Liu; Wenxiang Cai; Jue Chen; Shunying Yu; Min Zhao; Guan Ning Lin (Human Genetics, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Synthesis and biological evaluation of new thiazolyl-urea derivatives as potential dual C-RAF/FLT3 inhibitors - Zhi-Hua Zhang; Bi-Fan Zeng; Zhe-Xue Song; Ying-Yu Yang; Kai-yun Zhang; Xue Du; Lin-lin Zhang; Dong Cai (Medicinal Chemistry Research, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Acanthopagrus oconnorae , a new species of seabream (Sparidae) from the Red Sea - Lucía Pombo‐Ayora; Viktor N. Peinemann; Collin T. Williams; Song He; Yu Jia Lin; Yukio Iwatsuki; Donal D. C. Bradley; Michael L. Berumen (Journal of Fish Biology, 2022)
A new species of sparid fish, Acanthopagrus oconnorae , is described based on 11 specimens collected in the shallow (0–1 m depth) mangrove‐adjacent sandflats of Thuwal, Saudi Arabia. The new species is distinguished from its congeners by the following combination of characters: second anal‐fin spine 12.8%–16.6% of standard length (SL); 3½ scale rows between the fifth dorsal‐fin spine and lateral line; suborbital width 5.7%–6.7% of SL; eyes positioned at the anterior edge of the head, often forming a weakly convex break in an otherwise gently curved head profile, when viewed laterally; caudal fin light yellow with black posterior margin (approximately half of fin); anal fin dusky grey, with posterior one‐fifth of the fin light yellow; black streaks on inter‐radial membranes of anal fin absent. The most similar species to A. oconnorae is Acanthopagrus vagus , which differs by the presence of a w‐shaped anterior edge of the scaled predorsal area, a more acute snout and black streaks on the inter‐radial membranes of the anal fin. Phylogenetic placement and species delimitation of A. oconnorae are discussed based on COI, CytB and 16S sequences. It is hypothesized that ecology and behaviour explain how this species avoided detection despite its likely occurrence in coastal areas of the Red Sea with historically high fishing pressure.

Effects of soil organic matter components and iron aluminum oxides on aggregate stability during vegetation succession in granite red soil eroded areas - Zhe Lin; Zhi-gang Huang; Da-lan Liao; Wan-xia Huang; Juan Huang; Yu-song Deng (Journal of Mountain Science, 2022)

Fissistiganoids A and B: two new flavonoids from the Fissistigma tungfangense - Wan-Lin Zhong; Xue-Ming Zhou; Ji-Ling Yi; Xin-Ming Song; Bin Zhang; Jing-Yu Yang; Guang-Ying Chen (Natural Product Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Transcriptome Changes Induced by Botrytis cinerea Stress and Weighted Gene Co-expression Network Analysis (WGCNA) in Actinidia chinensis - Zhe-Xin Li; Wen-Lin Zhang; Deng-Wei Jue; Xia Liu; Yu-Song Jiang; Jian-Min Tang (Plant Molecular Biology Reporter, 2022)

Grazing by Tibetan Sheep Enhances Soil Bacterial and Fungal Diversity in Cold Season Pastures of Alpine Meadows on the Northern Qinghai–Tibetan Plateau - Lin Wang; Xiaojun Yu; Changlin Xu; Yuanyuan Jing; Meijuan Song (Journal of Soil Science and Plant Nutrition, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

Structure reassignment of two triterpenes with CASE algorithms and DFT chemical shift predictions - Zhi-Kang Duan; Tian-Ming Lv; Guan-Shan Song; Yu-Xi Wang; Bin Lin; Xiao-Xiao Huang (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

A new monoterpene-lactone with neuroprotective activity from corn silk - Wei-Yu Zhou; Tian-Ming Lv; Zi-Lin Hou; Ming Bai; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

High-throughput sequencing clarifies the spatial structures of microbial communities in cadmium-polluted rice soils - Li Song; Zhenzhi Pan; Yi Dai; Lin Chen; Li Zhang; Qilin Liao; Xiezhi Yu; Hongyan Guo; Guisheng Zhou (Environmental Science and Pollution Research, 2021)

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Screening of binding proteins that interact with two components of the HOG MAPK pathway by the yeast two-hybrid method in Colletotrichum siamense - Xiaomiao Liao; Xiping Long; Qiguang He; Miao Song; Xiao Li; Wenbo Liu; Yu Zhang; Chunhua Lin; Weiguo Miao (European Journal of Plant Pathology, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Adaptive Evolution of Chalcone Isomerase Superfamily in Fagaceae - Li-Mei Lin; Hong-Yu Guo; Xin Song; Duo-Duo Zhang; Yue-Hong Long; Zhao-Bin Xing (Biochemical Genetics, 2021)

RING-finger protein 5 promotes hepatocellular carcinoma progression and predicts poor prognosis - Yi Zhang; Jie Li; Huayang Chen; Changmao Zhang; Song You; Yue Zhao; Xiaoning Lin; Yaqi Yu; Fei Fang; Ting Fang; Xiaomin Wang (Human Cell, 2021)

Polycyclic aromatic hydrocarbon and n-alkane pollution characteristics and structural and functional perturbations to the microbial community: a case-study of historically petroleum-contaminated soil - Jian Li; Ying Xu; Quanwei Song; Jie Yang; Lin Xie; Shihang Yu; Lei Zheng (Environmental Science and Pollution Research, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

CAS-ESM2.0 Model Datasets for the CMIP6 Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) - Jiangbo Jin; He Zhang; Xiao Dong; Hailong Liu; Minghua Zhang; Xin Gao; Juanxiong He; Zhaoyang Chai; Qingcun Zeng; Guangqing Zhou; Zhaohui Lin; Yi Yu; et al. (Advances in Atmospheric Sciences, 2021)
The second version of the Chinese Academy of Sciences Earth System Model (CAS-ESM2.0) is participating in the Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) experiments in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The purpose of FAFMIP is to understand and reduce the uncertainty of ocean climate changes in response to increased CO 2 forcing in atmosphere-ocean general circulation models (AOGCMs), including the simulations of ocean heat content (OHC) change, ocean circulation change, and sea level rise due to thermal expansion. FAFMIP experiments (including faf-heat, faf-stress, faf-water, faf-all, faf-passiveheat, faf-heat-NA50pct and faf-heat-NA0ct) have been conducted. All of the experiments were integrated over a 70-year period and the corresponding data have been uploaded to the Earth System Grid Federation data server for CMIP6 users to download. This paper describes the experimental design and model datasets and evaluates the preliminary results of CAS-ESM2.0 simulations of ocean climate changes in the FAFMIP experiments. The simulations of the changes in global ocean temperature, Atlantic Meridional Overturning Circulation (AMOC), OHC., and dynamic sea level (DSL), are all reasonably reproduced.

CAS-ESM2.0 Model Datasets for the CMIP6 Ocean Model Intercomparison Project Phase 1 (OMIP1) - Xiao Dong; Jiangbo Jin; Hailong Liu; He Zhang; Minghua Zhang; Pengfei Lin; Qingcun Zeng; Guangqing Zhou; Yongqiang Yu; Mirong Song; Zhaohui Lin; Ruxu Lian; et al. (Advances in Atmospheric Sciences, 2021)
As a member of the Chinese modeling groups, the coupled ocean-ice component of the Chinese Academy of Sciences’ Earth System Model, version 2.0 (CAS-ESM2.0), is taking part in the Ocean Model Intercomparison Project Phase 1 (OMIP1) experiment of phase 6 of the Coupled Model Intercomparison Project (CMIP6). The simulation was conducted, and monthly outputs have been published on the ESGF (Earth System Grid Federation) data server. In this paper, the experimental dataset is introduced, and the preliminary performances of the ocean model in simulating the global ocean temperature, salinity, sea surface temperature, sea surface salinity, sea surface height, sea ice, and Atlantic Meridional Overturning Circulation (AMOC) are evaluated. The results show that the model is at quasi-equilibrium during the integration of 372 years, and performances of the model are reasonable compared with observations. This dataset is ready to be downloaded and used by the community in related research, e.g., multi-ocean-sea-ice model performance evaluation and interannual variation in oceans driven by prescribed atmospheric forcing.

Identification of 5S and 45S rDNA sites in Chrysanthemum species by using oligonucleotide fluorescence in situ hybridization (Oligo-FISH) - Jun He; Sisi Lin; Zhongyu Yu; Aiping Song; Zhiyong Guan; Weimin Fang; Sumei Chen; Fei Zhang; Jiafu Jiang; Fadi Chen; Haibin Wang (Molecular Biology Reports, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Illumina sequencing revealed roles of microRNAs in different aluminum tolerance of two citrus species - Yang-Fei Zhou; Yan-Yu Wang; Wei-Wei Chen; Li-Song Chen; Lin-Tong Yang (Physiology and Molecular Biology of Plants, 2020)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Roles of MicroRNA-122 in Cardiovascular Fibrosis and Related Diseases - Ying Liu; Jia-Wei Song; Jian-Yu Lin; Ran Miao; Jiu-Chang Zhong (Cardiovascular Toxicology, 2020)

CAS-FGOALS Datasets for the Two Interglacial Epochs of the Holocene and the Last Interglacial in PMIP4 - Weipeng Zheng; Yongqiang Yu; Yihua Luan; Shuwen Zhao; Bian He; Li Dong; Mirong Song; Pengfei Lin; Hailong Liu (Advances in Atmospheric Sciences, 2020)
Two versions of the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System model (CAS-FGOALS), version f3-L and g3, are used to simulate the two interglacial epochs of the mid-Holocene and the Last Interglacial in phase 4 of the Paleoclimate Modelling Intercomparison Project (PMIP4), which aims to study the impact of changes in orbital parameters on the Earth’s climate. Following the PMIP4 experimental protocols, four simulations for the mid-Holocene and two simulations for the Last Interglacial have been completed, and all the data, including monthly and daily outputs for the atmospheric, oceanic, land and sea-ice components, have been released on the Earth System Grid Federation (ESGF) node. These datasets contribute to PMIP4 and CMIP6 (phase 6 of the Coupled Model Intercomparison Project) by providing the variables necessary for the two interglacial periods. In this paper, the basic information of the CAS-FGOALS models and the protocols for the two interglacials are briefly described, and the datasets are validated using proxy records. Results suggest that the CAS-FGOALS models capture the large-scale changes in the climate system in response to changes in solar insolation during the interglacial epochs, including warming in mid-to-high latitudes, changes in the hydrological cycle, the seasonal variation in the extent of sea ice, and the damping of interannual variabilities in the tropical Pacific. Meanwhile, disagreements within and between the models and the proxy data are also presented. These datasets will help the modeling and the proxy data communities with a better understanding of model performance and biases in paleoclimate simulations.

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Disfiguring Mucor irregularis Infection Cured by Amphotericin B and Itraconazole: A Case Report and Treatment Experience - Lin-wei Wei; Hong Wang; Ying-gai Song; Jin Yu (Mycopathologia, 2019)

Isolation of a New PAK1 Gene from Sea Cucumber (Apostichopus japonicus) and Its Expression Analysis and Function Characterization - Liyuan Ren; Kaiquan Li; Yaoyao Zhan; Yi Wang; Yao Yu; Yang Chen; Kai Lin; Jian Song; Yaqing Chang (Journal of Ocean University of China, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

The roles of morphological traits, resource variation and resource partitioning associated with the dietary niche expansion in the fish‐eating bat Myotis pilosus - Yang Chang; Shengjing Song; Aoqiang Li; Yu Zhang; Zhongle Li; Yanhong Xiao; Tinglei Jiang; Jiang Feng; Aiqing Lin (Molecular Ecology, 2019)
Niche expansion and shifts are involved in the response and adaptation to environmental changes. However, it is unclear how niche breadth evolves and changes toward higher‐quality resources. Myotis pilosus is both an insectivore and a piscivore. We examined the dietary composition and seasonality in M . pilosus and the closely related Myotis fimbriatus using next‐generation DNA sequencing. We tested whether resource variation or resource partitioning help explain the dietary expansion from insects to fish in M . pilosus . While diet composition and diversity varied significantly between summer and autumn, the proportion of fish‐eating individuals did not significantly change between seasons in M . pilosus . Dietary overlap between M . pilosus and M . fimbriatus during the same seasons was much higher than within individual species across seasons. We recorded a larger body size, hind foot length, and body mass in M . pilosus than in M . fimbriatus and other insectivorous trawling bats from China. Similar morphological differences were found between worldwide fishing bats and nonfishing trawling bats. Our results suggest that variation in insect availability or interspecific competition may not play important roles in the dietary expansion from insects to fish in M . pilosus . Myotis pilosus has morphological advantages that may help it use fish as a diet component. The morphological advantage promoting dietary niche evolution toward higher quality resources may be more important than variation in the original resource and the effects of interspecific competition.

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Are glutamate transporters neuroprotective or neurodegenerative during cerebral ischemia? - Li-Nan Zhang; Liang Hao; Yu-Song Guo; Hai-Yan Wang; Lin-lin Li; Li-Zhe Liu; Wen-Bin Li (Journal of Molecular Medicine, 2019)

Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises - Hairong Yu; Lin Ye; Ganesh R. Naik; Rong Song; Hung T. Nguyen; Steven W. Su (Medical & Biological Engineering & Computing, 2018)

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

Meta-QTL analysis and identification of candidate genes related to root traits in maize - Jian Guo; Lin Chen; Yongxiang Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Yu Li; Tianyu Wang; Deguang Yang; Chunhui Li (Euphytica, 2018)

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Rapid classification of virgin and recycled EPS containers by Fourier transform infrared spectroscopy and chemometrics - Xue-Chao Song; Qin-Bao Lin; Yi-Cai Zhang; Zhong Li; Yu Zeng; Zhi-Feng Chen (Food Additives & Contaminants: Part A, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

FGF21 Attenuates High-Fat Diet-Induced Cognitive Impairment via Metabolic Regulation and Anti-inflammation of Obese Mice - Qingzhi Wang; Jing Yuan; Zhanyang Yu; Li Lin; Yinghua Jiang; Zeyuan Cao; Pengwei Zhuang; Michael J. Whalen; Bo Song; Xiao-Jie Wang; Xiaokun Li; Eng H. Lo; et al. (Molecular Neurobiology, 2018)

Berberine protects renal tubular cells against hypoxia/reoxygenation injury via the Sirt1/p53 pathway - Yuanbang Lin; Mingwei Sheng; Yijie Ding; Nan Zhang; Yayue Song; Hongyin Du; Ning Lu; Wenli Yu (Journal of Natural Medicines, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

The Expression of Dectin-1, Irak1 and Rip2 During the Host Response to Aspergillus fumigatus - Jinguo Liu; Lin Yu; Cuicui Chen; Jian Zhou; Xin Gong; Dandan Li; Dongni Hou; Yuanlin Song; Changzhou Shao (Mycopathologia, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Characterization and fine mapping of qkc7.03: a major locus for kernel cracking in maize - Mingtao Yang; Lin Chen; Xun Wu; Xing Gao; Chunhui Li; Yanchun Song; Dengfeng Zhang; Yunsu Shi; Yu Li; Yong-xiang Li; Tianyu Wang (Theoretical and Applied Genetics, 2018)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)

Influences of meteorological conditions on interannual variations of particulate matter pollution during winter in the Beijing–Tianjin–Hebei area - Jianjun He; Sunling Gong; Hongli Liu; Xingqin An; Ye Yu; Suping Zhao; Lin Wu; Congbo Song; Chunhong Zhou; Jie Wang; Chengmei Yin; Lijuan Yu (Journal of Meteorological Research, 2017)

Two reported cytotypes of the emergent orchid model species Erycina pusilla are two different species - Hsuan-Yu Yeh; Choun-Sea Lin; Hans de Jong; Song-Bin Chang (Euphytica, 2017)
Each species is characterized by a specific set of chromosomes, which is described as the chromosome portrait or karyotype. In general, such a karyotype is the same for all individuals in the population. An exception to that rule has recently been found in the orchid Erycina pusilla , which has been reported to have two cytotypes with chromosome numbers of 2n = 10 and 2n = 12. Here, we examined the karyotypes of the two cytotypes and found differences in arm ratios and heterochromatin patterns as well as in the presence of satellite chromosomes and in the number and location of rDNA and telomeric repeat sites. These differences are extensive and would have required multiple chromosome rearrangements to generate the differences between the two karyotypes. We also found that F1 hybrids between the parents with the two different chromosome numbers resulted in sterile offspring, in accordance with our previous findings. The combination of hybrid sterility and extensively rearranged chromosomes supports the hypothesis that these two reported cytotypes are, in fact, two different species.

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Retraction Note to: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly(ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Comparative genomics analysis of five Psychrobacter strains isolated from world-wide habitats reveal high intra-genus variations - Shan Zhang; Weizhi Song; Min Yu; Xuezheng Lin (Extremophiles, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Modeling and Manufacturing Technology for Personalized Biological Fixed Implants - Zhang Guoqing; Yang Yongqiang; Lin Hui; Song Changhui; Xiao Ran; Yu Jiakuo (Journal of Medical and Biological Engineering, 2017)

PM2.5 emissions from different types of heavy-duty truck: a case study and meta-analysis of the Beijing-Tianjin-Hebei region - Liying Song; Hongqing Song; Jingyi Lin; Cheng Wang; Mingxu Yu; Xiaoxia Huang; Yu Guan; Xing Wang; Li Du (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Tracking fluorescent components of dissolved organic matter from soils in large-scale irrigated area - Hongwei Pan; Huibin Yu; Yonghui Song; Lin Zhu; Ruixia Liu; Erdeng Du (Environmental Science and Pollution Research, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Migration of styrene and ethylbenzene from virgin and recycled expanded polystyrene containers and discrimination of these two kinds of polystyrene by principal component analysis - Qin-Bao Lin; Xue-Chao Song; Hong Fang; Yu-Mei Wu; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2017)

Both major and minor QTL associated with plant height can be identified using near-isogenic lines in maize - Xiaoyu Ding; Xun Wu; Lin Chen; Chunhui Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Zhizhai Liu; Yong-xiang Li (Euphytica, 2017)

Chemical treatment of contaminated sediment for phosphorus control and subsequent effects on ammonia-oxidizing and ammonia-denitrifying microorganisms and on submerged macrophyte revegetation - Juan Lin; Yufang Zhong; Hua Fan; Chaofeng Song; Chao Yu; Yue Gao; Xiong Xiong; Chenxi Wu; Jiantong Liu (Environmental Science and Pollution Research, 2017)

RETRACTED ARTICLE: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly (ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Prey selection and foraging behavior of the whelk Rapana venosa - Nan Hu; Fang Wang; Tao Zhang; Hao Song; Zheng-Lin Yu; Da-Peng Liu (Marine Biology, 2016)

Characterization of the spatial variability of soil available zinc at various sampling densities using grouped soil type information - Xiao-Dong Song; Gan-Lin Zhang; Feng Liu; De-Cheng Li; Yu-Guo Zhao (Environmental Monitoring and Assessment, 2016)

Synthesis and evaluation as potential antitumor agents of novel ursolic acid derivatives - Ming-Chuan Liu; Sheng-Jie Yang; Lin-Hong Jin; De-Yu Hu; Wei Xue; Song Yang (Medicinal Chemistry Research, 2016)

The relationships of meteorological factors and nutrient levels with phytoplankton biomass in a shallow eutrophic lake dominated by cyanobacteria, Lake Dianchi from 1991 to 2013 - Qichao Zhou; Yunlin Zhang; Dunmei Lin; Kun Shan; Yu Luo; Lei Zhao; Zhiwei Tan; Lirong Song (Environmental Science and Pollution Research, 2016)

Fine mapping of qKW7, a major QTL for kernel weight and kernel width in maize, confirmed by the combined analytic approaches of linkage and association analysis - Xin Li; Yong-xiang Li; Lin Chen; Xun Wu; Weiwei Qin; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Yunsu Shi (Euphytica, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

GSTM1 Null Genotype and GSTP1 Ile105Val Polymorphism Are Associated with Alzheimer’s Disease: a Meta-Analysis - Mo Wang; Yu Li; Lulu Lin; Guijun Song; Teng Deng (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Cytogenetic and cytometric analyses in artificial intercytotypic hybrids of the emergent orchid model species Erycina pusilla - Hsuan-Yu Yeh; Choun-Sea Lin; Song-Bin Chang (Euphytica, 2015)
Erycina pusilla is considered a potential model organism for orchids, because of several advantageous features, such as short juvenile period, low chromosome number and all year round blooming. Two different chromosome numbers (2n = 10 and 2n = 12) are reported for E. pusilla , which suggests two cytotypes. To reveal the genome homology between these two cytotypes, we generated hybrids from the intercytotypic reciprocal crosses (2n = 10 × 2n = 12 and 2n = 12 × 2n = 10), and applied 4′,6-diamidino-2-phenylindole staining, genomic in situ hybridization and flow cytometry for genomic and cytogenetic analysis. The parental genomes showed high similarity both in genomic composition and content. The hybrids displayed a chromosome number of 2n = 11 in mitotic cells. Moreover, five bivalents and one univalent were observed at meiotic metaphase I stage. We observed meiotic synaptic behavior and found homeologous pairing with unpaired loops between parental chromosome pairing segments. These results demonstrated that chromosome rearrangement events have occurred between parental cytotypes during evolution. This study also illustrated the genome homology and homeologous pairing at pachytene phase, indicating that the chromosome number variation of two cytotypes mainly resulted from chromosome rearrangements, not changes in genomic constitution.

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Physical regulation of stem cells differentiation into teno-lineage: current strategies and future direction - Jia Lin Chen; Wei Zhang; Ze Yu Liu; Boon Chin Heng; Hong Wei Ouyang; Xue Song Dai (Cell and Tissue Research, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

RIP1-dependent Bid cleavage mediates TNFα-induced but Caspase-3-independent cell death in L929 fibroblastoma cells - Guozhu Chen; Xiang Cheng; Ming Zhao; Song Lin; Jiangyang Lu; Jiarui Kang; Xiaodan Yu (Apoptosis, 2015)

Observation of the middle intestinal tight junction structure, cloning and studying tissue distribution of the four Claudin genes of the grass carp (Ctenopharyngodon idellus) - Fan Xu; Yuan-Tu Ye; Chun-Fang Cai; Ping Wu; Lin Song; Meng Liu; Lin-Jie Yao; Jiao-Jiao Dong; Yu-Wei Huang; Zhi Gong; Jie Qin; Liang Song (Fish Physiology and Biochemistry, 2014)

Effects and Mechanism of Action of Ligustrazine on Isoprenaline-Induced Cardiomyocyte Hypertrophy - Xuan Xiu Ji; Xiao Li Song; Wei Qian; Xiao Lin Yu; Jian You Zhu (Cell Biochemistry and Biophysics, 2014)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

The hiatus and accelerated warming decades in CMIP5 simulations - Yi Song; Yongqiang Yu; Pengfei Lin (Advances in Atmospheric Sciences, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Variants of COL3A1 Are Associated with the Risk of Stroke Recurrence and Prognosis in the Chinese Population: a Prospective Study - Wenfei Lv; Yahui Lin; Weihua Song; Kai Sun; Hui Yu; Yinhui Zhang; Channa Zhang; Liang Li; Miaomiao Suo; Rutai Hui; Jingzhou Chen (Journal of Molecular Neuroscience, 2014)

Composition of fish species in the Bering and Chukchi Seas and their responses to changes in the ecological environment - Longshan Lin; Yongjun Chen; Yunchih Liao; Jing Zhang; Puqing Song; Xingguang Yu; Risheng Wu; Kwang-tsao Shao (Acta Oceanologica Sinica, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Surface runoff and nitrogen (N) loss in a bamboo (Phyllostachys pubescens) forest under different fertilization regimes - Qichun Zhang; Imran Haider Shamsi; Jinwen Wang; Qiujin Song; Qiaoyun Xue; Yan Yu; Xianyong Lin; Sayed Hussain (Environmental Science and Pollution Research, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) samples from field cases in Fujian, China - Xi Chen; Jinxian Yang; Fusong Yu; Junqing Ge; Tianlong Lin; Tieying Song (Virus Genes, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

An alternative method for cDNA cloning from surrogate eukaryotic cells transfected with the corresponding genomic DNA - Lin-yong Hu; Chen-chen Cui; Yu-jie Song; Xiang-guo Wang; Ya-ping Jin; Ai-hua Wang; Yong Zhang (Biotechnology Letters, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Genomic sequencing and analysis of Chilli ringspot virus, a novel potyvirus - Dian Gong; Jian-Hua Wang; Zhan-Song Lin; Shao-Yan Zhang; Yu-Liang Zhang; Nai-Tong Yu; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2011)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

cDNA cloning and characterization of a new member of the tumor necrosis factor receptor family gene from scallop, Chlamys farreri - Jianguo Su; Limei Qiu; Ling li; Lin Liu; Lingling Wang; Vinu S. Siva; Dahui Yu; Linsheng Song (Molecular Biology Reports, 2011)

Factors affecting lipid accumulation by Nannochloropsis oculata in a two-stage cultivation process - Chia-Hung Su; Liang-Jung Chien; James Gomes; Yu-Sheng Lin; Yuan-Kun Yu; Jhang-Song Liou; Rong-Jhih Syu (Journal of Applied Phycology, 2011)

A method of urban ecological risk assessment: combining the multimedia fugacity model and GIS - Hui Min Song; Lin Yu Xu (Stochastic Environmental Research and Risk Assessment, 2011)

Artificial gynogenesis and assessment of homozygosity in meiotic gynogens of spotted halibut (Verasper variegatus) - Xiang-Shan Ji; Song-Lin Chen; Jing-Feng Yang; Hong-Yu Ma; Yun-Liang Jiang (Aquaculture International, 2010)

Biotransformation of eugenol by suspension cultures of transgenic crown galls of Panax quinquefolium and suspension cultures of Nicotiana tabacum - Lin Yang; Chunyan Yan; Jianhua Zhu; Liyan Song; Rongmin Yu (World Journal of Microbiology and Biotechnology, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Protein kinase C regulates neurite outgrowth in spinal cord neurons - Ping Yang; Zhen-Qiang Li; Lin Song; Yu-Qin Yin (Neuroscience Bulletin, 2010)

Berberine suppresses intestinal disaccharidases with beneficial metabolic effects in diabetic states, evidences from in vivo and in vitro study - Li Liu; Yun-Li Yu; Jian-Song Yang; Yang Li; Yao-Wu Liu; Yan Liang; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Construction of a Genetic Linkage Map and Mapping of a Female-Specific DNA Marker in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Xiaolin Liao; Hong-Yu Ma; Gen-Bo Xu; Chang-Wei Shao; Yong-Sheng Tian; Xiang-Shan Ji; Jing-Feng Yang; Song-Lin Chen (Marine Biotechnology, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Development of polymorphic microsatellite markers from barfin flounder (Verasper moseri) and their cross-species amplification - Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Hong-Yu Ma; Yong-Sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

Molecular Identification, Polymorphism, and Expression Analysis of Major Histocompatibility Complex Class IIA and B Genes of Turbot (Scophthalmus maximus) - Yu-Xi Zhang; Song-Lin Chen (Marine Biotechnology, 2006)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

A rice transcription factor OsbHLH1 is involved in cold stress response - Yu-Jun Wang; Zhi-Gang Zhang; Xin-Jian He; Hua-Lin Zhou; Yu-Xiang Wen; Ji-Xun Dai; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2003)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)